Kebijakan Pemerintah Kota Tanjungpinang dalam Pemungutan Pendapatan Asli Daerah melalui Sektor Pajak Daerah - Irwansyah; Shahril; Junriana; RICCO PUTRA NAMO (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
Tanjungpinang as the capital of Riau Islands province, a city which has the authority or regional autonomy it is necessary to set the region to create a policy / regulation, one of which related to the source of local revenue. it is extremely urgency in order not to completely rely on the central government. For local revenue based foundation law No. 28 of 2009 on taxes and levies, then there are sources for local governments to finance their own needs as stipulated in the legislation as above. In this study the focus is weeks to see how the government is trying to do in Tanjungpinang local taxation as an instrument of local revenue and see if there is a problem factor in the formulation of financial regulation Tanjungpinang city government to support revenue. regulatory and policy implementation Tanjungpinang city government is expected to provide financial regulation, especially for income Tanjungpinang city area, so that local autonomy given the freedom to provide broad authority to raise taxes. Tanjungpinang city government policy expected to mengekspolari potential of the region by making innovations.